The combined impact of cold smoking and natural antioxidants on quality and shelf life of dolphinfish (Coryphaena hippurus) fillets. Issue 4 (18th March 2019) - Messina, Concetta Maria; Bono, Gioacchino; Arena, Rosaria; Randazzo, Mariano; Morghese, Maria; Manuguerra, Simona; La Barbera, Laura; Ozogul, Fatih; Sadok, Saloua; Santulli, Andrea
Abstract: This study aimed to produce new value‐added products from dolphinfish ( Coryphaena hippurus ) as fillets when using cold smoking combined with natural antioxidants, obtained from Halocnemum strobilaceum a plant belonging to halophytes. The fillet treatments were controlled (untreated), immersed in standard brine (STD), treated with NaCI and antioxidant before freezing (Aox‐pre) and treated with NaCl and antioxidant after thawing (Aox‐post). The quality of dolphinfish fillets was assessed using sensory, biochemical, microbiological, and technological parameters. Treating fillets with antioxidants before freezing and cold smoking (Aox‐pre) enhanced significantly the shelf life, as well as improved the biochemical, microbiological, and sensory aspects of the product. Aox‐pre fillets had the lowest peroxide values (PV) and malondialdehyde (MDA) content, demonstrating that the immediate treatment of fillets with the polyphenols protected lipids from peroxidation. The smoking process, together with antioxidant treatment, significantly reduced microbial counts after 15 days of storage, compared to the control. Overall, combining antioxidant treatments with cold smoking has a positive effect on the quality of Aox‐pre fillets with respect to both sensory components and biochemical parameters associated with shelf life. Consequently, Aox‐pre treatment enhances the marketability of this species, promoting local and seasonal products, contributing to costal fisheries sustainability. Abstract : Cold smoking coupled with natural polyphenols improves quality and shelf life of dolphinfish fillets. This opportunity can ameliorate the marketability of this species, by adding value and realizing new products. Furthermore, this possibility can reduce pressure to target species contributing also to sustainability.